HybridP3M : Processes in Optimized, Mature Environments. - Rosinski, Lukasz (New York : Business Expert Press, 2021)
Hybrid P3M: Processes in Optimized, Mature Environments is an advanced technical book for hybrid project and program management. It is a complete methodology covering both processes as well as principles, according to a sound meta-model. Essentially, it combines the benefits of predictive and agile delivery and it aligns with the Projects with Learning Outcomes (ProwLO) methodology introduced in Knowledge Management for Project Excellence, by Lukasz Rosinski.
Cover -- Halftitle -- Title -- Copyright -- Description -- Contents -- Acknowledgments -- Introduction -- Chapter 1: Introduction to Processes -- Chapter 2: Method Foundation -- Chapter 3: Defining the Project/Program -- Chapter 4: Integrating Knowledge Management -- Chapter 5: Planning -- Chapter 6: Risk Management -- Chapter 7: Business Case Development -- Chapter 8: Realizing Benefits -- Chapter 9: Monitoring and Control -- Chapter 10: Managing Stakeholder Expectations -- Chapter 11: Managing Requirements -- Chapter 12: Evaluating the Project or Program -- Chapter 13: Leading the Project or Program -- Chapter 14: Project/Program Establishment -- Chapter 15: Providing Assurance -- Chapter 16: Agile Product Delivery -- Conclusion -- Appendix: Cases-Method -- References -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Project management; Agile project management; Leadership; Electronic books